SOCIAL AND MEDICAL FACTORS AFFECTING THE PERFORMANCE OF SCHOOL GOING CHILDREN - Ilyas, Muhammad; Jadoon, Huma; Ahmad, Nisar; Farooq, Saeed; Sarwar, Ghulam (Journal of Ayub Medical College Abbottabad, 1996)
This study was conducted in an English Medium School for evaluating the performance of school going children in light of various factors. The students belonging to business class had poor performance (68. 75%) as compared to Government Servant's Class in which 62.5% students had good performance. Those who were having irregular sleep (75%), playing hours (62.5%) timing of meal (87.5%), watching the T.V. programmes (87.5%) and reading newspapers, books and magazines (50%), showed poor performance, while the children having good performance were regular in their sleep (87.5 %), playing hours (100%), timing of meals (81%), watching the TV (94%), and reading newspapers, books and magazines (94%). It was further observed that the poor performance group was dependent upon tuition by some teacher while the good performance group was helped in study by the parents or other family members.